Illicit Trade in Gold Cultural Materials in Butuan, Philippines - Estrella, Victor P. (Kasarinlan: Philippine Journal of Third World Studies, 2020)
Historical and archaeological records have always associated Butuan in northeast Mindanao with gold. This reputation has set off rampant looting activities in and out of the locality since the 1970s until today. Such illicit activities have never been given much attention, and thus, this form of destruction of cultural properties has never been accounted for. This study examines the conduct of pag-aantik in Butuan through the lens of an archaeologist working on the site. I intend to expose the processes and the people involved in the illicit trade in gold cultural materials in this archaeologically rich market. Through the ethnography of looting, the study draws its attention to the social nature of the illicit trade. I argue that a small-scale analysis of this activity in Butuan allows us to observe interactions and relationships between groups of people, and the transformations gold items go through in the process. This is all to inform the academe as well as the future policies that aim to combat the destruction of cultural resources in the country.
Keywords: Butuan; illicit trade; gold artefacts; ethnography of looting